Representation and Sensation—A Defence of Deleuze's Philosophy of Painting. Issue 1 (2nd January 2016) - Somers-Hall, Henry
Abstract: Deleuze's philosophy of painting can be seen to pose certain challenges to a phenomenological approach to philosophy. While a phenomenological response to Deleuze's philosophy is clearly needed, I show in this article how an approach taken in a recent paper by Christian Lotz proves inadequate. Lotz argues that through Deleuze's refusal to accept the place of representation in art, he is unable to distinguish art from decoration, or to give a coherent account of how the (non-representational) content of art can be represented. I show that this criticism emerges from a misreading of the place of representation in Deleuze's philosophy. I will argue that by failing to take account of some of the key features of Deleuze's wider ontology, such as the importance of both the virtual and the actual for his analysis of objects, Lotz's critique proves unsuccessful. In particular, I want to show that Lotz's criticisms rest on a failure to attend to the systematic nature of Deleuze's philosophy, and in particular, the place of Deleuze's analysis of Bacon within the system as a whole. I will further show that Lotz's phenomenological defence commits the fallacy of petitio principii, assuming the validity of the phenomenological method in order to justify the phenomenological approach.